Capacity enhancement of an indoor visible light communication system using cooperative transmission. Issue 2 (1st April 2020) - Romero‐Munoz, Gabriela Alejandra; Lee, Kyesan; Kim, Changwoo; Han, Doohee
Abstract : This study investigates cooperative inter‐lighting interference cancellation (C‐ILIC) in indoor multiple‐input single‐output (MISO) visible light communication (VLC) to overcome co‐channel interference (CCI) and provide connectivity, even if there is link blockage. C‐ILIC exhibits great improvement in the average bit error rate (BER) performance and the transmission capacity. VLC plays an important role in handling the increasing data traffic in indoor environments. When the transmitters simultaneously send unique data over the same frequency resources, and the receiver obtains the different signals, CCI occurs because the signals interfere with each other. C‐ILIC employs cooperative transmission to forward a composite data, which consists of the high received power data and the low received power data, and ILIC to decode the high received power data and reduce CCI in the low received power data before decoding. Through computer simulations, the BER performance of C‐ILIC overcomes the conventional ILIC in any position because the receiver power ratio always complies with the threshold. Despite the BER performance deteriorating in the presence of link blockage, the data connection is guaranteed when the obstruction is not severe. Therefore, C‐ILIC can provide reliable communication and full connectivity within a room.